Adjuvant chemotherapy may improve disease‐free survival in patients with rectal cancer positive for MRI‐detected extramural venous invasion following chemoradiation. (June 2017) - Chand, M.; Rasheed, S.; Heald, R.; Swift, I.; West, N.; Rao, S.; Tekkis, P.; Brown, G.
Abstract: Aim: MRI‐detected extramural venous invasion (mrEMVI) is a poor prognostic factor in rectal cancer. Preoperative chemoradiotherapy (CRT) can cause regression in the severity of EMVI and subsequently improve survival whereas mrEMVI persisting after CRT confers an increased risk of recurrence. The effect of adjuvant chemotherapy (AC) following CRT on survival in rectal cancer remains unclear. The aim of this study was to determine whether there is a survival advantage for AC given to patients with mrEMVI persisting after CRT. Method: A prospective analysis was conducted of consecutive patients with locally advanced rectal cancer between 2006 and 2013. All patients underwent CRT followed by surgery. AC was given to selected patients based on the presence of specific 'high‐risk' features. Comparison was made between patients offered AC with observation alone. The primary outcome was 3‐year disease‐free survival (DFS). Results: Of 631 patients, 227 (36.0%) demonstrated persistent mrEMVI following CRT. Patients were grouped on the basis of AC or observation and were matched for age, performance status and final histopathological staging. Three‐year DFS in the AC group was 74.6% compared with 53.7% in the observation only group. AC had a survival benefit on multivariate analysis (hazard ratio 0.458; 95% CI: 0.271–0.775, P = 0.004). Conclusion: Patients with persistent mrEMVI following CRT who receive AC may have a decreased risk of recurrence and an improved 3‐year DFS compared with patients not receiving AC, irrespective of age and performance status.